Hardcore smoking after comprehensive smoke-free legislation and health warnings on cigarette packets in Hong Kong. (March 2016) - Leung, D.Y.P.; Chan, S.S.C.; Chan, V.; Lam, T.-H.
Abstract: Objective: To examine if there were changes in the proportion of hardcore smokers and factors associated with hardcore smoking before and after implementation of smoke-free legislation, and warning labels on cigarette packets in Hong Kong in January 2007. Study design: Repeated cross-sectional surveys of the general population in Hong Kong. Methods: Data from all daily smokers aged ≥15 years in the population-based Thematic Household Surveys from 2005 ( n  = 3740) and 2008 ( n  = 2958) were used to estimate the prevalence of hardcore smokers before and after implementation of smoke-free legislation. A logistic regression model was used to identify the factors associated with hardcore smoking, and to examine if there were any changes in their associations with the likelihood of hardcore smoking after implementation of smoke-free legislation. Results: The proportion of hardcore smokers among current daily smokers increased significantly from 22.5% [95% confidence interval (CI) 21.1–23.8%] in 2005 to 28.3% (95% CI 26.7–29.9%) in 2008. Change in the strength of the association of hardcore smoking with three factors was observed. The strength of the association between hardcore smoking and 'necessity in social functions' [odds ratio (OR) 0.54, 95% CI 0.31–0.95) and 'necessity for killing time' (OR 0.56, 95% CI 0.36–0.89) decreased, while the association between hardcore smoking and 'necessity as refreshment' increased (OR 3.02, 95% CI 1.43–6.39) after implementation of smoke-free legislation and warning labels on cigarette packets. 'Smoking had become a habit' was the factor associated most strongly with hardcore smoking (OR 4.88, 95% CI 4.02–5.93). Conclusions: The proportion of hardcore smokers remained stable in Hong Kong from 2005 to 2008. While the implementation of the two tobacco control measures may have provided an environment to reduce social smoking in hardcore smokers, addiction appeared to be the most important factor associated with hardcore smoking. More effective and tailor-made cessation services that target this group of smokers are needed. Highlights: Results did not support a hardening of the smoking have occurred in Hong Kong. Addiction appeared to be strongest predictor of hardcore smoking. Smoke-free legislation and package warning labels seemed to reduce social smoking.